An improved procedure for the preparation of Ru(bpz)3(PF6)2 via a high-yielding synthesis of 2,2’-bipyrazine - Schultz, Danielle M.; Sawicki, James W.; Yoon, Tehshik P. (Beilstein Journal of Organic Chemistry, 2015)
There has been a recent surge of interest in the use of transition metal polypyridyl complexes as visible light-absorbing photocatalysts for synthetic applications. Among the most attractive features of this approach is the availability of many known complexes with well-characterized photophysical and electrochemical properties. In particular, Ru(bpz)32+ is a powerful photooxidant that has proven to be uniquely suited for oxidatively induced photoredox transformations. We present here a straightforward and high-yielding route to Ru(bpz)3(PF6)2 that features an improved Pd-catalyzed synthesis of the 2,2’-bipyrazine ligand that is amenable to gram-scale preparations.
Keywords: heterocycles; ligand synthesis; palladium; photocatalysis; reductive coupling

(untitled) - Teplý, F. (Collect. Czech. Chem. Commun., 2011)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Reckenthäler, M.; Griesbeck, A. G. (Adv. Synth. Catal., 2013)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Kalyanasundaram, K. (Coord. Chem. Rev., 1982)

(untitled) - Juris, A.; Balzani, V.; Barigelletti, F.; Campagna, S.; Belser, P.; von Zelewsky, A. (Coord. Chem. Rev., 1988)

(untitled) - Flamigni, L.; Barbieri, A.; Sabatini, C.; Ventura, B.; Barigelletii, F. (Top. Curr. Chem., 2007)

(untitled) - Douglas, J. J.; Nguyen, J. D.; Cole, K. P.; Stephenson, C. R. J. (Aldrichimica Acta, 2014)

(untitled) - Crutchley, R. J.; Lever, A. B. P. (J. Am. Chem. Soc., 1980)

(untitled) - Haga, M.-A.; Dodsworth, E. S.; Eryavec, G.; Seymour, P.; Lever, A. B. P. (Inorg. Chem., 1985)

(untitled) - Lin, S.; Ischay, M. A.; Fry, C. G.; Yoon, T. P. (J. Am. Chem. Soc., 2011)

(untitled) - Tyson, E. L.; Ament, M. S.; Yoon, T. P. (J. Org. Chem., 2013)

(untitled) - Tyson, E. L.; Niemeyer, Z. L.; Yoon, T. P. (J. Org. Chem., 2014)

(untitled) - Parrish, J. D.; Ischay, M. A.; Lu, Z.; Guo, S.; Peters, N. R.; Yoon, T. P. (Org. Lett., 2012)

(untitled) - Lu, Z.; Parrish, J. D.; Yoon, T. P. (Tetrahedron, 2014)

(untitled) - Maity, S.; Zheng, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Maity, S.; Zhu, M.; Shinabery, R. S.; Zheng, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Nguyen, T. H.; Maity, S.; Zheng, N. (Beilstein J. Org. Chem., 2014)

(untitled) - MacQueen, D. B.; Schanze, K. S. (J. Am. Chem. Soc., 1991)

(untitled) - Vogler, C.; Schwederski, B.; Klein, A.; Kaim, W. (J. Organomet. Chem., 1992)

(untitled) - Alvila, L.; Pakkanen, T. A.; Krause, O. (J. Mol. Catal., 1993)

(untitled) - Schnebeck, R.-D.; Randaccio, L.; Zangrando, E.; Lippert, B. (Angew. Chem., Int. Ed., 1998)

(untitled) - Blake, A. J.; Champness, N. R.; Cooke, P. A.; Nicolson, J. E. B. (Chem. Commun., 2000)

(untitled) - Liberman-Martin, A. L.; Bergman, R. G.; Tilley, T. D. (J. Am. Chem. Soc., 2013)

(untitled) - Lafferty, J. J.; Case, F. H. (J. Org. Chem., 1967)

(untitled) - Rillema, D. P.; Allen, G.; Meyer, T. J.; Conrad, D. (Inorg. Chem., 1983)

(untitled) - Bronner, C.; Wenger, O. S. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Fort, Y.; Becker, S.; Caubère, P. (Tetrahedron, 1994)

(untitled) - Dhital, R. N.; Kamonsatikul, C.; Somsook, E.; Sakurai, H. (Catal. Sci. Technol., 2013)

(untitled) - Boully, L.; Turck, A.; Plé, N.; Darabantu, M. (J. Heterocycl. Chem., 2005)

(untitled) - Monserrat, K.; Foreman, T. K.; Grätzel, M.; Whitten, D. G. (J. Am. Chem. Soc., 1981)

(untitled) - Elliot, C. M.; Hershenhart, E. J. (J. Am. Chem. Soc., 1982)

(untitled) - Furue, M.; Maruyama, K.; Oguni, T.; Naiki, M.; Kamachi, M. (Inorg. Chem., 1992)

(untitled) - McFarland, S. A.; Cheng, K. A. W. Y.; Lee, F. S.; Cozens, F. L.; Schepp, N. P. (Can. J. Chem., 2008)

(untitled) - Takizawa, S.-y.; Shimada, K.; Sato, Y.; Murata, S. (Inorg. Chem., 2014)

(untitled) - Plé, N.; Turck, A.; Heynderickx, A.; Quéguiner, G. (Tetrahedron, 1998)